Self-reported visual difficulties in Europe and related factors: a European population-based cross-sectional survey - Leveziel, Nicolas; Marillet, Simon; Braithwaite, Tasanee; Peto, Tunde; Ingrand, Pierre; Pardhan, Shahina; Bron, Alain M.; Jonas, Jost B.; Resnikoff, Serge; Little, Julie-Anne; Bourne, Rupert R. A. (Acta ophthalmologica, 2021)
Purpose There is a relative paucity of self-reported vision problems data in European countries. Methods In this context, we investigated self-reported vision problems through European Health Interview Survey 2, a cross-sectional European population survey based on a standardized questionnaire including 147 medical, demographic and socioeconomic variables applied to non-institutionalized individuals aged 15 years or more in 28 European countries, in addition to Iceland and Norway. Results The survey included 311 386 individuals (54.18% women), with overall crude prevalence of self-reported vision problems of 2.07% [95% CI; 2.01-2.14]. Among them, 1.70 % [1.61-1.78] of men, 2.41% [2.31-2.51] of women and 4.71% [4.53-4.89] of individuals aged 60 or more reported to have a lot of vision problems or to be not able to see. The frequency of self-reported vision problems was the highest in Eastern European countries with values of 2.43% [2.30-2.56]. In multivariate analyses, limiting long-standing illness, depression, daily smoking, lack of physical activity, lower educational level and social isolation were associated with self-reported vision problems with ORs of 2.66 [2.42-2.92], 2.16 [2.01-2.32], 1.11 [1.01-1.23], 1.31 [1.21-1.42], 1.29 [1.19-1.40] and 1.45 [1.26-1.67], respectively, while higher income was associated with less self-reported vision problems with OR of 0.80 [0.73-0.86]. Conclusions This study demonstrated inequalities in terms of prevalence of self-reported vision problems in Europe, with higher prevalence in Eastern European countries and among women and older individuals.
Online publiziert: 7. Oktober 2020
Gesehen am 04.03.2025